2019
DOI: 10.1111/cts.12648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid‐Suppressive Strategies on Pazopanib Efficacy in Patients With Soft‐Tissue Sarcoma

Abstract: Pazopanib (PAZ), a tyrosine kinase inhibitor used in the treatment of soft tissue sarcoma (STS), should not be administered with acid‐suppressive medications (ASMs) due to decreased drug solubility. Common practice for patients requiring ASM with PAZ is to separate administration by 12 hours; however, there is little real‐world evidence describing clinical outcomes using this strategy. The aim of this study was to determine whether concomitant ASM impacted efficacy and adverse event rates in patients with STS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…A retrospective analysis of two prospective studies of pazopanib in STS (EORTC 62,043 and 62072) demonstrated that gastric-acid suppressive agents (GAS) concomitantly administrated (in 17.7% of the 333 eligible patients) was associated with shorter mPFS (2.8 vs. 4.6 months (HR, 1.49; 95% CI, 1.11-1.99; p = 0.01)), and mOS (8.0 vs. 12.6 months (HR, 1.81; 95% CI, 1.31-2.49; p < 0.01)); these effects were not observed in placebo-treated patients [9]. This was also shown in another series of patients treated for STS [10]. Surprisingly, two retrospective series analyzing pazopanib in advanced RCC patients gave negative results, with only minor differences in prognosis between patients receiving PPIs or not receiving them [11,12].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A retrospective analysis of two prospective studies of pazopanib in STS (EORTC 62,043 and 62072) demonstrated that gastric-acid suppressive agents (GAS) concomitantly administrated (in 17.7% of the 333 eligible patients) was associated with shorter mPFS (2.8 vs. 4.6 months (HR, 1.49; 95% CI, 1.11-1.99; p = 0.01)), and mOS (8.0 vs. 12.6 months (HR, 1.81; 95% CI, 1.31-2.49; p < 0.01)); these effects were not observed in placebo-treated patients [9]. This was also shown in another series of patients treated for STS [10]. Surprisingly, two retrospective series analyzing pazopanib in advanced RCC patients gave negative results, with only minor differences in prognosis between patients receiving PPIs or not receiving them [11,12].…”
Section: Discussionsupporting
confidence: 51%
“…A pooled retrospective analysis, comparing patients treated for STS in two prospective trials with pazopanib or placebo, with or without the associated PPIs, showed a reduction in PFS and overall survival (OS) in patients who were concomitantly on PPIs and pazopanib (no effect was observed in the placebo arm), suggesting a detrimental role for this combination [9]. Another retrospective study from medical records, in a cohort of 91 patients treated with pazopanib for STS, demonstrated that the 42 patients taking concomitant acid-suppressive medications had shorter PFS and a trend toward less hypertension [10]. Conversely, two retrospective studies of patients on pazopanib for advanced RCC did not show any change in survival when pazopanib was combined with PPIs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the DDIs between PPIs and TKIs; the results are contradictory concerning PPI interaction with the bioavailability and activity of TKIs. A summary of these DDIs is presented in Table 3 ( Rugo et al, 2005 ; Egorin et al, 2009 ; Yin et al, 2010 ; Yin et al, 2012 ; Takahashi et al, 2012 ; Hilton et al, 2013 ; Abbas et al, 2013 ; Musib et al, 2013 ; Tan et al, 2013 ; Johansson et al, 2014 ; Narasimhan et al, 2014 ; Chu et al, 2015 ; Kletzl et al, 2015 ; Ha et al, 2015 ; Iurlo et al, 2016 ; Kumarakulasinghe et al, 2016 ; Lam et al, 2016 ; Zenke et al, 2016 ; Chu et al, 2017 ; Lalani et al, 2017 ; Lacy et al, 2017 ; Lau et al, 2017 ; Morcos et al, 2017 ; Yokota et al, 2017 ; de Jong et al, 2018 ; Nieves Sedano et al, 2018 ; Ohgami et al, 2018 ; Fang et al, 2019 ; Mir et al, 2019 ; Vishwanathan et al, 2018 ; Pisano et al, 2019 ; de Man et al, 2019 ; Koutake et al, 2020 ; Ruanglertboon et al, 2020 ; Van De Sijpe et al, 2020 ; Chen et al, 2021 ; Rassy et al, 2021 ). Table 4 summarizes the main studies reporting reductions in the survival of patients receiving this combination of medication ( Chu et al, 2015 ; Ha et al, 2015 ; Fang et al, 2019 ; Mir et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study following patients who were prescribed erlotinib while also taking a proton pump inhibitor (PPI) or a histamine-2 receptor antagonist (H 2 RA) concomitantly found a reduced progression-free survival compared with the group taking erlotinib alone (5.3 months vs. 11.0 months, p = .029; Lam et al, 2016 ). Pazopanib (Votrient) is another example of an OC that is impacted by pH ( Pisano et al, 2019 ). Patients with soft-tissue sarcoma taking concomitant GAS agents and pazopanib therapy experienced a shorter progression-free survival relative to patients taking pazopanib alone (5.3 months vs. 6.7 months; Pisano et al, 2019 ).…”
Section: Ddis Related To Gastric Acid Suppressionmentioning
confidence: 99%
“…Pazopanib (Votrient) is another example of an OC that is impacted by pH ( Pisano et al, 2019 ). Patients with soft-tissue sarcoma taking concomitant GAS agents and pazopanib therapy experienced a shorter progression-free survival relative to patients taking pazopanib alone (5.3 months vs. 6.7 months; Pisano et al, 2019 ). Patients taking an H 2 RA were counseled to take their pazopanib dose 2 hours before or 10 hours after their H 2 RA dose, but pazopanib efficacy was still decreased ( Pisano et al, 2019 ).…”
Section: Ddis Related To Gastric Acid Suppressionmentioning
confidence: 99%